Economics of grids, clouds, systems, and services : 13th international conference, GECON 2016, Athens, Greece, September 20-22, 2016, revised selected papers /: 13th international conference, GECON 2016, Athens, Greece, September 20-22, 2016, revised selected papers. (2019) - Unknown
No abstract available